ACCURACY EMPATHY OF STUDENT COLLEGE OF JAVA TRIBE AND SUNDA TRIBE - Sutanti, Tri (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2020)
This study aims to describe the accuracy of empathy in Javanese and Sundanese students from the Guidance and Counseling Study Program at Ahmad Dahlan University. Samples were taken by purposive sample with 60 students consisting of 30 Javanese students and 30 Sundanese students. The instrument used was empathy accuracy scale. The study results were analyzed using descriptive statistical analysis and different tests with Anova. The results showed that the accuracy of empathy among Javanese and Sundanese students had a significant value of 0.821 0.05, which means there was no significant difference between the accuracy of empathy among Javanese and Sundanese students. This research also reveals that the highest aspect of empathy accuracy in Javanese students is emotional concern, while Sundanese students are perspective taking. This means that the accuracy of empathy among Javanese students is higher in understanding and feeling the emotional of others, while the accuracy of empathy of Sundanese students is higher in understanding and placing themselves in the minds of others. The results of this study can be used as a base for developing techniques and strategies in guidance and counseling services that focus on developing accuracy of empathy in adolescents